2015
DOI: 10.2527/jas.2015-8962
|View full text |Cite
|
Sign up to set email alerts
|

Postweaning substitution of grazed forage with a high-energy concentrate has variable long-term effects on subcutaneous fat and marbling in Bos taurus genotypes1

Abstract: ABSTRACT:The objective of this study was to quantify the effects and interactions of stage of growth and genotype on commercial carcass traits and intramuscular fat (IMF) content in 5 muscles of Bos taurus steers (n = 165) and to test the hypothesis that substituting pasture with a high-energy concentrate during the immediate postweaning period increases IMF. Cattle of 3 genotypes (Angus, Hereford, and Wagyu × Angus; n = 55/genotype) were selected at weaning from commercial herds, targeting genotypic differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…The basic experimental details relating to this animal trial have been previously reported [12]. In brief we studied 15 individual 259 day grain fed Angus, Hereford and Wagyu x Angus steers (n = 5 per breed) slaughtered at~26 months of age as part of the larger experiment detailed by [12]. Management was standardised for all individuals during growth on pasture from weaning through long-feedlotting.…”
Section: Beef Cooperative Research Centre III Marbling and Fat Distrimentioning
confidence: 99%
See 3 more Smart Citations
“…The basic experimental details relating to this animal trial have been previously reported [12]. In brief we studied 15 individual 259 day grain fed Angus, Hereford and Wagyu x Angus steers (n = 5 per breed) slaughtered at~26 months of age as part of the larger experiment detailed by [12]. Management was standardised for all individuals during growth on pasture from weaning through long-feedlotting.…”
Section: Beef Cooperative Research Centre III Marbling and Fat Distrimentioning
confidence: 99%
“…Management was standardised for all individuals during growth on pasture from weaning through long-feedlotting. For the transcriptome analysis of the fat depots we focussed on animals' pasture-fed only during the immediate post-weaning period, rather than animals that received supplement during the immediate post-weaning period [12].…”
Section: Beef Cooperative Research Centre III Marbling and Fat Distrimentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest was an indication of very elevated activity of the cholesterol 25 hydroxylase enzyme in the IMF depot. A suite of oxysterol metabolites were quantitated in plasma using mass spectrometry and appear to be promising circulating biomarkers for whole carcass IMF content.MethodsBeef CRCIII marbling and fat distribution experimentThe basic experimental details relating to this animal trial have been previously reported[12]. In brief we studied 15 individual 259 day grain fed Angus, Hereford and Wagyu x Angus steers (n = 5 per breed) slaughtered at ~26 months of age as part of the larger experiment detailed by[12].…”
mentioning
confidence: 99%